Organic flow battery with high energy density and preparation method thereof
By adopting optimized electrochemical oxidation reaction conditions and purification methods, solvent-induced self-assembly technology, oxygen plasma treatment and plasma oxidation activation technology in organic liquid flow batteries, problems such as low solubility of the positive electrode material, cyclic precipitation, and out-of-control hydration expansion of the separator are solved, and a battery with high energy density and long-term performance is achieved.
Patent Information
- Application Number
- CN202510345646.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-06-20
AI Technical Summary
In existing organic flow batteries, the low solubility of the positive electrode material, the circulating precipitation leads to battery attenuation, the out-of-control hydration expansion of the separator, the uneven distribution of electrode catalytic activity, and the neglected impact of the pH of the electrolyte.
Optimized electrochemical oxidation reaction conditions and purification methods were used to prepare high-purity positive electrode active materials, and the solubility of the positive electrode active materials was regulated through solvent-induced self-assembly technology, oxygen plasma treatment was used to enhance the ionic conductivity of the SPEEK film, and nitrogen-doped graphene/carbon nanotube composite electrode materials were treated through plasma oxidation activation technology.
It significantly improves the cycle stability and energy density of the battery, reduces internal resistance, enhances the power density and long-term performance of the battery, and solves problems such as low solubility of the positive electrode material, cyclic precipitation, and out-of-control diaphragm hydration expansion.
Smart Images

Figure CN120184304A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic flow batteries, and particularly to a high-energy-density organic flow battery and a preparation method thereof. Background Art
[0002] As a technology for large-scale energy storage, flow batteries have received increasing attention in recent years. Its core components include positive and negative electrode materials, electrolytes, separators, and catalytic electrodes, which determine the efficiency and lifespan of the overall battery. The positive electrode material usually adopts a reversible redox pair, such as a fully organic system or a metal complex system, to improve the energy density and cycle stability. The separator is responsible for selective ion transport, preventing cross-contamination of the electrolytes, and at the same time affecting the internal resistance and overall efficiency of the battery. The role of the catalytic electrode is to reduce the reaction activation energy and increase the charge transfer rate, thereby enhancing the power output of the battery.
[0003] However, the dissolution ability of a single solvent system is limited, the solubility cannot be increased, and precipitation is inevitable. Improper selection of the solvent often leads to the loss of activity of the positive electrode material after long-term cycling, affecting the battery lifespan. Even if the initial performance seems good, after hundreds of cycles, the precipitates accumulate little by little, and ultimately become a hidden danger to stability. Moreover, the hydration swelling of traditional separators is poorly controlled. If too much water is absorbed, the size changes greatly, the mechanical strength decreases, and the battery lifespan is shortened accordingly. If too little water is absorbed, the proton conductivity cannot be increased, the transport efficiency is low, resulting in an increase in the internal resistance of the battery and a decrease in the overall performance. It is difficult to balance the two, and it is difficult to find the best balance point in practical applications. Summary of the Invention
[0004] In view of the deficiencies of the prior art, the present invention provides a high-energy-density organic flow battery and a preparation method thereof, which solve the problems of low solubility of the positive electrode material, battery attenuation caused by cyclic precipitation, out-of-control hydration swelling of the separator, uneven distribution of electrode catalytic activity, and the neglect of the influence of the pH of the electrolyte in the prior art.
[0005] To achieve the above objectives, the present invention is realized through the following technical solutions: A high-energy-density organic flow battery includes a positive electrode electrolyte, a negative electrode electrolyte, an electrolyte solution, an ion exchange membrane, and electrode materials, wherein:
[0006] The positive electrode electrolyte contains a positive electrode active substance, and its chemical structural formula is C 14 H8F6N2, which contains trifluoromethyl and cyano substituents on the molecular skeleton, and the mass fraction is 2.0 - 5.0 wt%.
[0007] Molecular Structure of the Positive Electrode Active Material: The molecule adopts an aromatic heterocyclic system, which has a strong electron delocalization effect, improving the reversibility of oxidation-reduction. The trifluoromethyl group (-CF3) is a strong electron-withdrawing group, which can lower the LUMO energy level of the molecule, making its oxidized state more stable and contributing to the improvement of the charge-discharge cycle life. The cyano group (-CN) is also an electron-withdrawing group, and its function is to further enhance the charge distribution uniformity of the molecule, improve solubility, and reduce intermolecular π-π stacking, optimizing the charge transport performance.
[0008] Oxidation-Reduction: The oxidation-reduction reaction of this molecule mainly involves the electron transfer process of the aromatic heterocycle. During charging, the molecule loses electrons to form a stable oxidized state, and during discharging, electrons are provided by the electrolyte to reduce it back to the initial state, forming a reversible cycle. This electron transfer kinetic process determines the electrochemical stability and cycle life of the positive electrode material.
[0009] The negative electrode electrolyte contains the negative electrode active material tetramethylpyridinium salt TMP + , and its structural formula is C9H 14 N + , with a mass fraction of 1.5 - 4.0 wt%;
[0010] Structural Characteristics of the Negative Electrode Material: TMP + is a pyridine derivative. The molecular stability is improved by tetramethyl substitution, and the possibility of self-polymerization is reduced. This molecular structure can maintain a relatively low radical recombination energy during the oxidation-reduction process, enabling efficient electron transfer.
[0011] Oxidation-Reduction: TMP + , as the negative electrode material, receives electrons during charging to form the TMP· radical, and loses electrons during discharging to return to TMP + . Since this system has a large conjugated system and uniform electron distribution, high oxidation-reduction reversibility can be achieved, the probability of side reactions can be reduced, and the cycle stability can be improved.
[0012] The electrolyte solution contains 1.0 - 2.0 M of NaClO4 as the supporting electrolyte, and a mixed solvent system of 10% - 20% DMSO + H2O, and the volume fraction of DMSO does not exceed 25%;
[0013] Function of the Supporting Electrolyte: NaClO4, as the supporting electrolyte, functions to provide high ionic conductivity and does not react with the electrode active material in side reactions. Na + and ClO4 - have a large hydration radius and are not prone to precipitation or deposition, which is beneficial to the stability of the system.
[0014] Solvent Optimization Design: A mixed solvent system of DMSO + H2O is adopted. As a highly polar organic solvent, DMSO can effectively improve the solubility of the positive and negative active materials, reduce the deposition risk of the active materials on the electrode surface, and improve the cycle stability. However, excessive DMSO leads to the swelling effect of the ion exchange membrane, affecting the ion transport efficiency of the battery. Therefore, this solution limits the volume fraction of DMSO to no more than 25% to achieve a balance between solubility and membrane stability.
[0015] The ion exchange membrane is a sulfonated polyaryletherketone membrane with a sulfonation degree of 30% - 50%;
[0016] Reasons for membrane material selection: SPEEK has good chemical stability, and its sulfonic acid groups (-SO3H) provide high proton conduction ability. At the same time, it can effectively block the cross-contamination of the positive and negative active materials and reduce self-discharge.
[0017] Influence of sulfonation degree: The sulfonation degree determines the hydrophilicity and ion transport ability of the SPEEK membrane. When the sulfonation degree is too low (<30%), the ionic conductivity of the membrane is low, which will affect the output power of the battery; when the sulfonation degree is too high (>50%), the mechanical strength of the membrane decreases, resulting in unstable structure. Therefore, the sulfonation degree is limited between 30% - 50% to ensure the balance of the mechanical stability and ionic conductivity of the membrane.
[0018] The electrode material is a nitrogen-doped graphene / carbon nanotube composite material with a nitrogen doping concentration of 2 - 10 at%, and its surface resistance is reduced to 3 - 5 Ω·cm after plasma oxidation activation treatment 2 ;
[0019] Rationality of material selection: The composite structure of graphene and carbon nanotubes can provide high conductivity and large specific surface area, enabling the active materials to fully contact the electrode surface and improving the rate of redox reactions. Nitrogen doping (N-doping) can introduce additional active sites, enhance the catalytic performance of the electrode, and increase the electron transfer rate.
[0020] Function of plasma oxidation activation: Plasma treatment can introduce oxidation groups (such as -OH, C=O) on the material surface, thereby increasing surface hydrophilicity, improving the wettability of the electrolyte and the interfacial stability of the electrode. In addition, plasma activation can reduce the electrode surface resistance to 3 - 5 Ω·cm 2 , ensuring rapid electron transport, reducing polarization loss, and improving the overall power density of the battery.
[0021] Preferably, the redox potential range of the positive electrode active material is 1.2 - 1.3V, and the redox potential range of the negative electrode active material is -0.5 to -0.8V, so that the theoretical working voltage of the battery reaches 1.5 - 2.0V.
[0022] Redox potential matching: The output voltage of an organic flow battery directly depends on the redox potential difference between the positive and negative electrode materials. For the positive electrode potential of 1.2 - 1.3V, a reasonable electron acceptor molecule is selected, which can provide strong oxidation ability. For the negative electrode potential of -0.5 to -0.8V, a stable electron donor molecule is selected to ensure efficient electron transfer during discharge. This can avoid an increase in side reactions caused by too strong an oxidant or a hydrogen evolution side reaction caused by too low a reducing agent while ensuring high energy density.
[0023] Optimization of battery voltage to 1.5 - 2.0V: The operating voltage of traditional aqueous flow batteries is usually limited to about 1.2V (for all-vanadium flow batteries), while in this solution, by reasonably screening redox couples, the battery voltage can be increased to 1.5 - 2.0V, which significantly improves the energy density. A higher battery voltage means that more energy can be stored per unit volume or mass, thus enhancing the overall performance of the energy storage system.
[0024] Reversibility of redox reactions: In the selected potential range, the redox reactions of the positive and negative electrode active substances are both in the reversible range, avoiding decomposition, polymerization or side reactions caused by too high or too low potentials, and improving the cycle stability of the battery. The optimization of the potential makes the entire electrochemical system more stable, can reduce the voltage decay during charge and discharge, and thus extends the service life of the battery.
[0025] Preferably, the electrolyte solution further comprises a solubility enhancer of 0.1 - 0.5M LiTFSI or a pH regulator of 0.1 - 0.5M H2SO4 or NaOH.
[0026] Function of LiTFSI: LiTFSI is a common solubility enhancer. Its role in an organic flow battery is to significantly increase the solubility of the organic electrolyte in the electrolyte solution. As a supporting electrolyte, LiTFSI provides higher ionic conductivity, which helps to improve the overall efficiency of the battery. LiTFSI also has a low hydrogen ion concentration and is not easily involved in side reactions with active substances, so it can be stably present in the electrolyte solution for a long time. It can not only enhance solubility but also improve the conductivity of the electrolyte solution, reduce impedance loss, and increase the power density of the battery.
[0027] Function of pH regulator: In the application of organic flow batteries, the pH value has an important influence on the stability of the electrolyte solution and the surface state of the electrode materials. By introducing a pH regulator, H2SO4 or NaOH, the acidity and alkalinity of the electrolyte solution can be effectively controlled, the ionization state of the electrolyte solution can be optimized, the conductivity of the electrolyte solution can be improved, and the passivation or dissolution reaction on the electrode surface can be avoided.
[0028] H2SO4 acts as an acidic regulator, which helps to provide higher ionic conductivity and maintain a stable redox reaction even in a low pH environment.
[0029] NaOH acts as a basic regulator, which can improve the solubility of some electrolytes. Especially in the negative electrode reaction, it can effectively enhance the solubility and reduce the deposition or crystallization problems of the negative electrode material during the cycling process, thereby enhancing the cycle life of the battery.
[0030] Synergistic effect of solubility enhancement and pH adjustment: By simultaneously using a solubility enhancer and a pH regulator in the electrolyte solution, the ionic balance of the electrolyte can be controlled while optimizing the solubility. Good solubility can not only improve the energy density of the battery, but also reduce the crystallization accumulation problems on the ion exchange membrane and the electrode surface, thereby enhancing the stability and long-term performance of the battery. The pH balance of the electrolyte helps to avoid solvent decomposition and unnecessary side reactions, thus extending the battery life and improving its working efficiency.
[0031] Preferably, the ion exchange membrane adopts a plasma surface treatment process with a treatment time of 2 - 10 min and a power of 50 - 200 W to optimize the ion conductivity and reduce the cross-contamination of active substances.
[0032] Effect of plasma surface treatment on the ion exchange membrane: Plasma treatment can introduce active functional groups (-OH, -COOH, -SO3H) on the surface of the ion exchange membrane, thereby increasing the hydrophilicity of the membrane and improving the transport rate of protons or ions in the membrane. Through the oxidation of plasma, the microstructure of the membrane can be optimized, the ionic conductivity of the membrane can be improved, the ion transport inside the battery can be made smoother, and the ohmic polarization loss can be reduced.
[0033] Optimization of treatment time and power:
[0034] Too short treatment time (<2 min) results in insufficient modification, insufficient introduction of functional groups on the membrane surface, and insignificant improvement in ionic conductivity;
[0035] Too long treatment time (10 min) or too high power (200 W) will cause over-oxidation and even damage to the membrane surface, reduce the mechanical strength of the membrane, and affect the long-term use stability;
[0036] Therefore, this solution selects a treatment range of 2 - 10 min and 50 - 200 W to achieve a balance between the improvement of ionic conductivity and the structural stability of the membrane.
[0037] Reduction of cross-contamination of active substances: Plasma treatment can form a functionalized layer on the membrane surface, making the membrane selective to specific ions (Na + 、ClO4 -) The selectivity is improved, thereby reducing the cross - penetration of the positive and negative active materials, reducing the self - discharge effect, and improving the Coulomb efficiency and cycle stability of the battery.
[0038] A preparation method of the organic flow battery based on the above, comprising the following steps:
[0039] S1. Dissolve 2 - amino - 3 - trifluoromethylpyridine (C6H4F3N2) and 1,2 - dibromobenzene (C6H4Br2) in a solvent, add a catalyst and carry out an electrochemical oxidation reaction to synthesize the positive active material BTFQ;
[0040] Function of the electrochemical oxidation reaction: During this reaction process, 2 - amino - 3 - trifluoromethylpyridine (C6H4F3N2) serves as a precursor molecule, and undergoes a coupling reaction with 1,2 - dibromobenzene (C6H4Br2) under the action of a catalyst to form a BTFQ molecule (aromatic heterocyclic structure) with an extended conjugated system. This conjugated system improves the electron delocalization effect, making BTFQ have high redox reversibility.
[0041] Functions of trifluoromethyl (-CF3) and cyano (-CN): During the synthesis process, -CF3, as a strong electron - withdrawing group, can lower the LUMO energy level of the molecule and improve the stability of the oxidation state. The introduction of -CN helps to enhance the solubility of the molecule, reduce the π - π stacking between molecules, and improve the charge transfer efficiency of the positive electrode material.
[0042] S2. Prepare the positive electrode electrolyte by solvent - induced self - assembly technology, and prepare a 1.0 - 2.0 M NaClO4 electrolyte solution;
[0043] Function of the solvent - induced self - assembly technology: This method uses the polarity and solvation of the solvent to regulate the self - assembly behavior of BTFQ molecules in the solution, enabling them to form a stable solution system and avoiding precipitation or aggregation phenomena. This technology can optimize the intermolecular interactions, improve the solubility of the active material in the electrolyte, and ensure the stability of the electrochemical reaction.
[0044] Function of NaClO4 as an electrolyte: NaClO4, as a supporting electrolyte with high conductivity, can improve the ionic conductivity of the electrolyte solution, and is not prone to side reactions with the active material, ensuring the efficient operation of the battery. ClO4 - has a relatively large hydration radius, which can reduce membrane fouling and improve the Coulomb efficiency of the battery.
[0045] S3. Use a sulfonated polyaryletherketone membrane as the ion - exchange membrane, and carry out plasma surface treatment;
[0046] Advantages of SPEEK as an ion exchange membrane: Due to its -SO3H (sulfonic acid group) structure, SPEEK can provide high ionic conductivity, effectively block the cross - contamination of positive and negative active materials, reduce the self - discharge effect, and improve the battery cycle stability.
[0047] Functions of plasma surface treatment: Plasma treatment can introduce oxidation functional groups (-OH, -COOH, -SO3H) on the membrane surface, further enhance the hydrophilicity of the membrane, and improve the proton conductivity. At the same time, this treatment process can also optimize the micro - pore structure of the membrane, improve the ion selectivity, reduce the cross - penetration of active materials, and improve the Coulomb efficiency of the battery.
[0048] S4. Use nitrogen - doped graphene / carbon nanotubes as the electrode material and carry out plasma oxidation activation treatment;
[0049] Functions of N - G / CNTs composite materials: Graphene provides high electronic conductivity, while carbon nanotubes enhance the structural stability and specific surface area, enabling active materials to be evenly distributed and improving the efficiency of electrochemical reactions. Nitrogen doping (N - doping) can introduce active sites, enhance the electron transfer rate, and improve the wettability of the electrode, strengthening the interaction with the electrolyte.
[0050] Functions of plasma oxidation activation: Plasma treatment can introduce oxidation functional groups, improve the hydrophilicity of the electrode surface, and optimize the interfacial wetting performance. At the same time, this treatment process can reduce the surface resistance of the electrode to 3 - 5 Ω·cm 2 , ensure rapid electron transfer, reduce polarization loss, and improve the power density and energy efficiency of the battery.
[0051] S5. Assemble an organic flow battery.
[0052] Overall optimization of the battery: Through the above - optimized positive and negative active materials, electrolyte solution, ion exchange membrane, and electrode materials, a high - performance organic flow battery is finally assembled. The redox potentials of the positive and negative electrode materials are reasonably matched, enabling the theoretical working voltage of the battery to reach 1.5 - 2.0V, much higher than that of traditional aqueous flow batteries (1.2V).
[0053] Improvement of system stability: The optimized electrode and membrane materials reduce the internal resistance of the battery, improve the energy conversion efficiency, while reducing the cross - contamination and side reactions of active materials, and extending the cycle life of the battery.
[0054] Preferably, the electrochemical oxidation reaction in S1 is carried out at a current density of 0.5–2.0 mA / cm 2 , the reaction temperature is controlled at 50–80 °C, the stirring time is 4–6 h, and purification is carried out by column chromatography or recrystallization to increase the purity of the positive electrode active material to >98%.
[0055] Optimization conditions for the electrochemical oxidation reaction:
[0056] Current density (0.5–2.0 mA / cm 2 ): This current density range controls the reaction rate, enabling it to effectively drive the oxidation reaction without generating side reactions too quickly or causing the decomposition of active substances. A lower current density helps improve the selectivity of the reaction and avoid over-oxidation.
[0057] Reaction temperature (50–80 °C): An increase in temperature accelerates the reaction process, increases the movement rate of reactant molecules, and helps with electron transfer and the progress of the coupling reaction. At the same time, temperature control avoids possible side reactions at too high a temperature, ensuring high purity and stability of the product.
[0058] Stirring time (4–6 h): An appropriate stirring time can ensure the uniform mixing of reactants, help improve the reaction efficiency and conversion rate, and prevent local temperature or concentration deviations. Too short a stirring time may lead to incomplete reactions, while too long may cause solvent evaporation or the formation of by-products.
[0059] Purification effects of column chromatography and recrystallization:
[0060] Column chromatography: Column chromatography separates and purifies the target product by utilizing the differences in the affinity of different substances for the stationary phase. It can effectively remove impurities and by-products, thereby improving the purity of the cathode active material, ensuring that its redox activity is not interfered with, and achieving ideal performance.
[0061] Recrystallization: By selectively dissolving different substances in a solvent, the target substance is recrystallized to separate impurities. Recrystallization can remove impurities that are difficult to separate by column chromatography, further improve the purity, and ensure the structural stability and reaction activity of the product.
[0062] Preferably, in S2, the solvent-induced self-assembly technique is adopted. By regulating the solvent composition and stirring rate of 200 - 500 rpm, the solubility of the cathode active material is optimized to ensure a solubility > 1.8 M.
[0063] Function of the solvent-induced self-assembly technique: The solvent-induced self-assembly technique relies on the polarity and solubility characteristics of the solvent to regulate the self-assembly behavior of the cathode active material (BTFQ). In this method, the selective distribution and interaction of the solvent can guide the assembly state of the active material in the solution, avoiding precipitation or aggregation phenomena. This technique optimizes the intermolecular interactions of the cathode material, improves its solubility in the electrolyte, and thus ensures the stability and efficiency of the battery reaction.
[0064] Some solvents can enhance the solubility of organic molecules through intermolecular hydrogen bonding or ionization, enabling them to be evenly distributed in the solution, thus ensuring the smooth progress of the electrochemical reaction.
[0065] Effect of stirring rate (200 - 500 rpm): The stirring rate controls the uniformity of the solution. Too low a stirring rate leads to incomplete dissolution, forming an unstable solution, while too high a stirring rate can cause bubbles or unnecessary solvent evaporation, and even result in local temperature imbalance. By controlling the stirring rate within the range of 200 - 500 rpm, the dissolution process can be effectively promoted, enabling the molecules of the positive electrode active material to be evenly distributed, increasing the solubility, preventing the precipitation of insoluble substances, and optimizing the stability of the solution.
[0066] Solubility optimization (1.8 M): The improvement of solubility directly affects the conductivity of the electrolyte and the overall performance of the battery. At higher solubility, the positive electrode active material can exist in a higher concentration in the electrolyte, thus providing more active material for the electrochemical reaction and increasing the energy density of the battery. A solubility exceeding 1.8 M ensures the sufficient distribution of the active material in the electrolyte, which is crucial for improving the cycle stability and long-term performance of the battery.
[0067] Preferably, in S3, the sulfonated polyaryletherketone membrane is treated with oxygen plasma for an optimized time of 2 - 10 min, and the ionic conductivity of the treated membrane is increased to 0.05 - 0.1 S / cm.
[0068] Effect of oxygen plasma treatment on the SPEEK membrane:
[0069] Introduction of active functional groups: Oxygen plasma treatment introduces active functional groups (-OH, -COOH, -SO3H) on the membrane surface through the action of high-energy oxygen atoms. The presence of these functional groups can enhance the hydrophilicity of the membrane, promote the adsorption and diffusion of water molecules in the membrane, and thus improve the proton or ion conduction efficiency.
[0070] Optimization of the microstructure: Plasma treatment can improve the microscopic pore structure on the membrane surface, making it more suitable for ion passage without significantly increasing the penetration of the active material. Such a structural adjustment ensures that the membrane has high selectivity and good mechanical strength.
[0071] Effect of treatment time (2 - 10 min):
[0072] Too short treatment time (<2 min): Insufficient introduction of functional groups, insignificant modification effect of the membrane, and limited increase in ionic conductivity.
[0073] Too long a treatment time (10 min): leads to excessive oxidation of the membrane, weakening its mechanical strength, and even causing membrane degradation. Therefore, a treatment time of 2-10 minutes is an optimal range that balances the improvement of ionic conductivity and the long-term stability of the membrane.
[0074] Improvement of ionic conductivity (0.05-0.1S / cm):
[0075] Through oxygen plasma treatment, the proton conduction path of SPEEK membrane becomes more continuous and efficient, and its ion conductivity is significantly improved. The conductivity range of 0.05-0.1S / cm indicates that the membrane has reached an efficient conduction state, which is of great significance for reducing the ohmic polarization of the battery and improving the power density.
[0076] Comprehensive optimization of selectivity and stability: Oxygen plasma treatment can enhance the selectivity of the membrane for specific ions while improving ionic conductivity, reducing cross-contamination of positive and negative active materials. This selectivity optimization effectively improves the coulombic efficiency of the battery, reduces the waste of active materials, and extends the service life of the battery.
[0077] Preferably, in S4, the nitrogen-doped graphene / carbon nanotube composite electrode material is treated by plasma oxidation activation technology, the treatment power is 50-200W, and the specific surface area after treatment reaches 500-800m 2 / g.
[0078] The role of plasma oxidation activation technology: Plasma treatment can introduce oxidative functional groups (-OH, -COOH, -C=O) on the surface of the material, effectively improving the wettability and hydrophilicity of the electrode material, making it easier to fully contact with the electrolyte, thereby improving the charge transfer efficiency. In addition, oxidation treatment can regulate the surface electronic structure, optimize catalytic activity, and improve the reaction kinetics of the electrode.
[0079] Increase in specific surface area (500-800m 2 / g):
[0080] Graphene and carbon nanotubes themselves have highly ordered nanoscale structures, but untreated materials may have more agglomeration, resulting in limited specific surface area.
[0081] Through plasma oxidation activation, nano-scale micropores can be formed on the surface of the material, and part of the graphite layer can be peeled off to make its structure more open, increasing the specific surface area to 500-800m 2 / g, significantly improving the charge storage capacity and ion diffusion efficiency of the electrode.
[0082] Impact of processing power (50-200W):
[0083] Low power (<50 W): Insufficient oxidation modification, few introduced functional groups, and limited improvement in the hydrophilicity and catalytic activity of the material.
[0084] High power (200 W): Causes structural damage to the carbon material, generates too many defects, reduces conductivity, and may lead to loss of some active sites.
[0085] Selecting a treatment range of 50 - 200 W can ensure an appropriate introduction of surface functional groups in the material, while maintaining good conductivity and structural integrity, enabling the electrode material to maintain stable performance under high power density conditions.
[0086] Synergistic effect of nitrogen doping (N-doping) and plasma oxidation:
[0087] Nitrogen doping can introduce active sites such as pyridinic-N and graphitic-N into the carbon skeletons of graphene and carbon nanotubes. These sites can effectively improve the electron transfer ability of the electrode and enhance the reversibility of the redox reaction.
[0088] After plasma oxidation, these active sites can further interact with the oxidized functional groups, optimize the surface charge distribution of the electrode, improve its adsorption ability for active substances, and reduce electrode polarization.
[0089] Preferably, the assembly of the battery includes:
[0090] Filling the positive electrode electrolyte and the negative electrode electrolyte into the corresponding liquid storage tanks respectively;
[0091] Transporting the electrolyte to the flow cell through pipelines;
[0092] Using a sulfonated polyaryletherketone membrane as the separator and a nitrogen-doped graphene / carbon nanotube composite material as the electrode, assembling the battery and conducting charge-discharge tests.
[0093] Function of the flow cell structure and electrolyte transportation:
[0094] The design of the flow cell enables the electrolyte to circulate continuously, ensuring the continuous supply of active substances, improving the reaction efficiency, and avoiding local concentration deviation.
[0095] The pipeline transportation uses highly corrosion-resistant materials (PTFE or FEP pipelines) to ensure that the electrolyte does not react with the pipe wall during transportation. At the same time, the flow rate is optimized to make the active substances evenly distributed, reduce the flow dead zone, and improve the energy conversion efficiency.
[0096] Function of the sulfonated polyaryletherketone membrane (SPEEK) as the separator:
[0097] The sulfonic acid group (-SO3H) structure of the membrane provides high ion selectivity, enabling efficient conduction of protons or other ions while blocking the cross-contamination of the positive and negative active materials, reducing the self-discharge effect, and improving the Coulombic efficiency of the battery.
[0098] After oxygen plasma treatment, the membrane surface is further optimized to improve hydrophilicity and ionic conductivity (0.05 - 0.1 S / cm), ensuring efficient ion exchange performance while maintaining chemical stability.
[0099] Functions of the nitrogen-doped graphene / carbon nanotube (N-G / CNTs) composite electrode:
[0100] The high specific surface area (500 - 800 m 2 / g) provides sufficient active sites, enhancing the adsorption capacity of the electrode for active materials and reducing the polarization impedance.
[0101] Nitrogen doping (N-doping) forms active sites (such as pyridine nitrogen and graphitic nitrogen), optimizing the electronic structure, increasing the electron transfer rate, and accelerating the redox reaction kinetics.
[0102] Plasma oxidation activation treatment introduces functional groups (-OH, -COOH) on the electrode surface, enhancing the wettability between the electrode and the electrolyte, improving the interfacial reaction efficiency, and reducing the electrode contact resistance.
[0103] Functions of charge-discharge tests:
[0104] Through constant current charge-discharge tests, key performance indicators such as the charge-discharge capacity, energy efficiency, and Coulombic efficiency of the battery are evaluated.
[0105] Electrochemical impedance spectroscopy (EIS) is used to analyze the ionic conductivity of the membrane, the interfacial impedance, and the charge transfer resistance of the electrode, ensuring low internal resistance and high stability of the overall system.
[0106] Long cycle life tests are conducted to observe the stability of active materials, the durability of the separator, and the corrosion resistance of electrode materials, in order to optimize the long-term use performance of the battery.
[0107] The present invention provides a high-energy density organic flow battery and its preparation method. It has the following
[0108] Beneficial effects:
[0109] 1. The present invention adopts optimized electrochemical oxidation reaction conditions and purification methods, achieving the technical effect of improving the purity of the positive electrode active material. Compared with the relatively rough purification methods in the prior art, the problems of insufficient purity and the influence of by-products are solved, significantly enhancing the cycle stability and energy conversion efficiency of the battery.
[0110] 2. The present invention regulates the solubility of the cathode active material through a solvent-induced self-assembly technique, ensuring a high solubility of >1.8 M in the electrolyte, thereby significantly improving the reaction efficiency and energy density of the battery. Compared with traditional dissolution methods, this solution can better prevent the precipitation and aggregation of the active material, ensuring long-term performance and stability.
[0111] 3. The present invention uses oxygen plasma treatment on the SPEEK membrane to optimize the ionic conductivity and hydrophilicity of the membrane. Compared with traditional membrane materials, the present invention can significantly improve the proton conductivity of the membrane, thereby effectively reducing the internal resistance, enhancing the power density and cycle stability of the battery, and solving the problem of insufficient conductivity of the membrane material.
[0112] 4. The present invention processes the nitrogen-doped graphene / carbon nanotube composite electrode material through a plasma oxidation activation technique, enhancing its specific surface area and catalytic activity. Compared with traditional electrode materials, the present invention effectively improves the charge storage capacity and ion diffusion efficiency of the electrode, solves the problems of slow electrode reaction rate and polarization, and significantly enhances the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0113] Figure 1 It is a schematic flow chart of the method of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0114] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0115] Example 1: Optimize the electrochemical oxidation reaction to improve the purity of the cathode active material:
[0116] Reaction formula (mass fraction %):
[0117] Target organic compound (BTFQ precursor): 40%;
[0118] Electrolyte (H2SO4 solution, 1.0 M): 58%;
[0119] Catalyst (RuO2 / Ti electrode): 2%.
[0120] Reaction conditions:
[0121] Current density: 1.2 mA / cm 2 ;
[0122] Temperature: 65 °C;
[0123] Stirring time: 5 h.
[0124] Purification steps:
[0125] Column chromatography (stationary phase: silica gel, eluent: ethyl acetate / n - hexane 2:1);
[0126] Recrystallization (solvent: acetonitrile, crystallization temperature: - 10 °C).
[0127] Example 2: Solvent - induced self - assembly to optimize the solubility of the cathode active material:
[0128] Formulation (mass fraction %):
[0129] BTFQ active material: 30%;
[0130] Solvent system (DMSO / acetonitrile 3:2 volume ratio): 70%.
[0131] Self - assembly conditions:
[0132] Stirring rate: 400 rpm;
[0133] Temperature: 45 °C;
[0134] Stirring time: 3 h.
[0135] Example 3: Oxygen plasma treatment of SPEEK membrane to improve ionic conductivity: SPEEK membrane treatment steps:
[0136] Oxygen plasma treatment, power 120 W, time 5 min;
[0137] Washing: ultrasonic cleaning with deionized water for 10 min;
[0138] Drying: vacuum drying at 80 °C for 2 h.
[0139] Example 4: Plasma oxidation activation of nitrogen - doped graphene / carbon nanotube composite electrode: Preparation of composite electrode (mass fraction %):
[0140] Graphene (N - doped): 50%;
[0141] Carbon nanotubes (CNTs): 30%;
[0142] Binder (PVDF): 10%;
[0143] Conductive agent (SuperP): 10%.
[0144] Plasma oxidation activation:
[0145] Treatment power: 100 W;
[0146] Treatment time: 8 min;
[0147] Gas environment: O2 / Ar (volume ratio 8:2).
[0148] Example 5: Complete battery assembly and testing:
[0149] Battery assembly steps:
[0150] Positive electrode electrolyte: The optimized formula of Example 2 is adopted and filled into the liquid storage tank;
[0151] Negative electrode electrolyte: Water-soluble organic active substance (1.5M solution);
[0152] Pipeline system: PTFE corrosion-resistant pipeline, flow rate 10 mL / min;
[0153] Separator: The SPEEK membrane treated by oxygen plasma in Example 3;
[0154] Electrode: The N-G / CNTs composite material in Example 4;
[0155] Flow cell assembly: Electrode area 25 cm 2 , electrolyte flow rate 12 mL / min.
[0156] Comparative Example 1: Preparation of positive electrode active material by traditional chemical oxidation method (corresponding to Example 1): Reaction formula (mass fraction %):
[0157] BTFQ precursor: 40%;
[0158] Strong oxidant (Na2S2O8): 15%;
[0159] H2SO4 solution (1.0M): 45%.
[0160] Reaction conditions:
[0161] Temperature: 60 °C;
[0162] Reaction time: 4 h;
[0163] Stirring rate: 300 rpm.
[0164] Purification method:
[0165] Solvent extraction method (ethyl acetate / water system, volume ratio 1:1);
[0166] Vacuum drying at 80 °C for 8 h.
[0167] Comparative Example 2: Dissolving positive electrode active material in a single solvent system (corresponding to Example 2):
[0168] Formula (mass fraction %):
[0169] BTFQ active material: 30%;
[0170] Single solvent (DMSO): 70%.
[0171] Stirring conditions:
[0172] Stirring rate: 300 rpm;
[0173] Temperature: 40 °C;
[0174] Stirring time: 2 h.
[0175] Comparative Example 3: Untreated SPEEK membrane (corresponding to Example 3):
[0176] Membrane preparation:
[0177] SPEEK is directly applied without additional oxygen plasma treatment;
[0178] The membrane is immersed in 1.0 M H2SO4 solution for 12 h;
[0179] Vacuum drying at 80 °C for 4 h.
[0180] Comparative Example 4: N-G / CNTs composite electrode without plasma oxidation activation (corresponding to Example 4):
[0181] Composite electrode preparation (mass fraction %):
[0182] N-G (untreated): 50%;
[0183] CNTs (untreated): 30%;
[0184] Binder (PVDF): 10%;
[0185] Conductive agent (SuperP): 10%.
[0186] Electrode forming:
[0187] Slurry preparation: Dispersed in NMP solvent and ultrasonicated for 30 min;
[0188] Doctor blading: Coated on carbon paper substrate;
[0189] Drying: At 120 °C for 6 h.
[0190] Comparative Example 5: Unoptimized traditional flow battery assembly (corresponding to Example 5):
[0191] Battery components:
[0192] Positive electrolyte: BTFQ active material dissolved in the single solvent system in Comparative Example 2;
[0193] Negative electrolyte: 1.0 M water-soluble organic active material solution;
[0194] Diaphragm: Use the untreated SPEEK diaphragm in Comparative Example 3;
[0195] Electrode: Use the unactivated N-G / CNTs composite material in Comparative Example 4.
[0196] Assembly steps:
[0197] Flow cell structure: The same design
[0198] Electrolyte flow rate: 12 mL / min.
[0199] Experiment 1, Comparative experiment on the purity of the positive electrode active material (Example 1 vs. Comparative Example 1):
[0200] Experimental purpose:
[0201] Evaluate the improvement effect of the optimized electrochemical oxidation method on the purity of the positive electrode active material, and compare the limitations of the traditional chemical oxidation method in by-product control.
[0202] Experimental steps:
[0203] Preparation of Sample A (Example 1):
[0204] Prepare 40 g of BTFQ precursor and dissolve it in 58 g of 1.0 M H2SO4 solution.
[0205] Use a RuO2 / Ti electrode as the anode, and set the current density to 1.2 mA / cm 2 , and control the reaction temperature at 65 °C.
[0206] Stir the reaction for 5 hours.
[0207] After the reaction, cool the solution, perform column chromatography purification (silica gel packing, ethyl acetate / n-hexane = 2:1), and then recrystallize (acetonitrile, -10 °C).
[0208] Preparation of Sample B (Comparative Example 1):
[0209] Mix the same amount of BTFQ precursor with H2SO4 solution (45%) and add Na2S2O8 (15%) as the oxidant.
[0210] Control the temperature at 60 °C and stir for 4 hours.
[0211] After the reaction, extract the product with ethyl acetate / water (1:1) solvent and dry it under vacuum at 80 °C for 8 hours.
[0212] Analysis method:
[0213] Use HPLC to analyze the purity (detection wavelength: 280 nm) and record the main peak area ratio.
[0214] Nuclear magnetic resonance (1 The by-product components were further identified by 1H-NMR).
[0215] Cyclic voltammetry (CV) was used to test its redox activity (scan rate: 50 mV / s, potential range: -0.5 V - 1.2 V vs Ag / AgCl).
[0216] Table 1: Purity and by-product analysis results of cathode active materials prepared by different oxidation methods
[0217]
[0218] Electrochemical oxidation is not simply an alternative reaction path. Essentially, it guides the gradual transformation of target functional groups by controlling current and potential. Side reaction paths are restricted, reaction selectivity is higher, and the generation of impurities is controlled. Once the oxidant is in excess or the reaction is uneven in traditional chemical oxidation, by-products immediately accumulate and the reaction system becomes uncontrollable. The decrease in purity is not accidental but a defect in the mechanism itself.
[0219] Moreover, the electrode interface reaction is milder. Reactants are guided to be oxidized as soon as they approach the electrode surface. Steric hindrance and electronic effects are involved simultaneously, and the orderliness is significantly enhanced. This electrochemical selectivity activates the reaction path, making side reactions almost ineffective, and side peaks rarely appear in NMR.
[0220] The HPLC peak shape is sharp, and the main peak ratio is far higher than that of traditional samples. The redox potential is also more stable. The CV curve shows high symmetry, and the electrochemical activity is not interfered by impurities. This is not just an improvement in purity but an essential enhancement of the activity itself. The structure is more regular, charge transfer is smoother, and the entire reaction system is "reconstructed" into a more efficient system.
[0221] Experiment 2: Solubility comparison experiment of cathode active materials (Example 2 vs Comparative Example 2):
[0222] Experiment purpose:
[0223] This experiment aims to verify whether solvent-induced self-assembly can effectively improve the solubility of cathode active materials and avoid the precipitation problems common in traditional solvent systems, thereby optimizing the stability of the cathode electrolyte.
[0224] Experiment steps:
[0225] Preparation of Sample A (Example 2):
[0226] Prepare the solvent system: Add 30 g of BTFQ active material to a DMSO / acetonitrile (mass ratio 3:1) solution.
[0227] Stir at 40 °C for 3 hours to ensure complete dissolution.
[0228] Filter to remove insoluble substances in the solution and keep the solution stable.
[0229] Preparation of Sample B (Comparative Example 2):
[0230] Using a single solvent DMSO, 30 g of BTFQ active substance was dissolved in 70 g of DMSO.
[0231] Stir for 2 hours and observe whether the dissolution process is complete.
[0232] Let it stand for 24 hours and observe whether there is any precipitate formed in the solution.
[0233] Solubility determination:
[0234] Solutions with different concentrations were prepared, and the saturation solubility was measured using a UV-Visible spectrophotometer (UV-Vis).
[0235] Let the solution stand for 24 hours, observe whether there is precipitation, take photos for record and measure the amount of precipitate.
[0236] Compare the solubility stability of different solutions at 60 °C.
[0237] Flow battery performance test:
[0238] Two electrolytes, A and B, were used to fill the flow battery respectively, and 100 charge-discharge cycle experiments were carried out, and the average value was taken.
[0239] Record the stability of the electrolyte during the cycling process, and test the capacity retention rate of the battery and the precipitation of the electrolyte.
[0240] Table 2: Comparative data on the solubility and precipitation of the positive electrode active substance
[0241]
[0242] Using a mixed solvent system (DMSO / acetonitrile) significantly improved the solubility, and no precipitation phenomenon was found. The reason for this phenomenon can be attributed to the effect of solvent-induced self-assembly. Acetonitrile played an auxiliary dissolution and stabilization role, effectively inhibiting the intermolecular interaction of BTFQ active substance molecules and avoiding the precipitation of supersaturated solution.
[0243] In contrast, in the system using a single solvent (DMSO), although the solubility was high, the amount of by-products precipitated increased significantly. As a polar solvent, DMSO has strong dissolution ability, but lacks additional auxiliary effects, which easily leads to the stacking of active substance molecules and the formation of crystals, thus reducing the solubility stability and battery performance. This indicates that a single solvent has natural limitations in terms of solubility and stability, and cannot provide additional structural stability like a mixed solvent system.
[0244] Experiment 3: Comparative Experiment on Ionic Conductivity of Membranes (Example 3 vs Comparative Example 3):
[0245] Purpose of the experiment:
[0246] This experiment aims to evaluate the effect of oxygen plasma treatment on the SPEEK membrane, mainly focusing on its improvement effect on ionic conductivity, hydration swelling rate and oxidation resistance stability, so as to verify whether the optimized membrane is more suitable for the flow battery system.
[0247] Experimental procedure:
[0248] Preparation of Sample A (Example 3):
[0249] The SPEEK membrane was cut into a size of 3 cm × 3 cm.
[0250] It was placed in an oxygen plasma reaction chamber (power 50 W, treatment time 90 s) to form an oxygen-functionalized surface.
[0251] Subsequently, the membrane was immersed in 1.0 M H2SO4 solution for 12 h to ensure complete hydration.
[0252] Finally, it was vacuum dried at 80 °C for 4 h to balance the water content.
[0253] Preparation of Sample B (Comparative Example 3):
[0254] The SPEEK membrane was directly used without oxygen plasma treatment.
[0255] Other treatment processes were the same as those of Sample A, including H2SO4 immersion and vacuum drying.
[0256] Ionic conductivity test:
[0257] The Nyquist plot was recorded using electrochemical impedance spectroscopy (EIS), and the surface resistance and proton conductivity were calculated.
[0258] Hydration swelling rate test:
[0259] After weighing the dry membrane, it was immersed in deionized water for 24 h, taken out and weighed. At the same time, the hydration swelling rate was calculated.
[0260] Oxidation resistance stability test:
[0261] A 1 cm × 1 cm membrane piece was taken and placed in 1.0 M H2O2 solution for 48 h.
[0262] The color change was observed, the mass loss rate was measured, and the oxidation degradation was evaluated.
[0263] Long cycle test:
[0264] The constant current charge-discharge mode was adopted at 50 mA / cm2 At a current density, 1000 charge-discharge cycles were carried out.
[0265] Every 200 cycles, the discharge specific capacity, energy efficiency and Coulomb efficiency were recorded.
[0266] Cycling stability evaluation:
[0267] Calculate the capacity retention rate after 500 and 1000 cycles, and analyze the attenuation trend of the material during long-term operation.
[0268] Observe the change of the electrode surface morphology and analyze the structural stability of the catalytic layer.
[0269] Table 3: Influence of oxygen plasma treatment on the performance of SPEEK separator
[0270]
[0271]
[0272] The role of oxygen plasma is far more than surface modification. It reshapes the structure of the separator at the nanoscale. The introduction of oxygen functional groups not only improves the hydration ability, but also forms additional proton transport channels, making the overall conductivity jump to the level of 130 mS / cm. This improvement is not simply to increase hydrophilicity, but through surface energy regulation, making the arrangement of water molecules more orderly and improving the proton migration efficiency. This effect is particularly obvious in the Nyquist plot of EIS. For the membrane treated with oxygen plasma, its low-frequency impedance is significantly reduced, indicating that the ion transport path is more unobstructed.
[0273] On the other hand, the untreated SPEEK separator has a significantly higher hydration swelling rate, approaching 50%. This means that its deformation is uncontrollable, which may lead to size instability and even a decrease in mechanical strength during the long-term operation of the battery. For the separator modified with oxygen plasma, the hydration swelling rate is reduced to about 38%, indicating that its structure is denser, the hydration is more uniform, and the problem of local over-expansion is avoided. In addition, the data of the oxidation resistance experiment also illustrate the advantages of the modified separator. Oxygen plasma treatment enhances the anti-degradation ability of the membrane, making its mass loss rate after being soaked in H2O2 for 48 h less than 2.5%, which is more than doubled compared with the untreated sample, indicating that the membrane is more stable in a strong oxidation environment.
[0274] The samples after plasma oxidation show excellent stability during long cycling. Even after 1000 charge-discharge cycles, the capacity retention rate remains above 92%, while the capacity of the untreated samples drops rapidly, remaining only about 73%-75%. This shows that plasma oxidation not only optimizes the initial catalytic activity, but also inhibits the decline of the electrode structure during long-term operation.
[0275] In terms of the attenuation rate, the average attenuation rate of the treated samples is only 0.007%-0.008% / cycle, far lower than that of the untreated samples which is above 0.025%. Long cycle tests also show that the electrodes of the untreated samples suffered relatively serious structural damage in the high-pH electrolyte, with partial peeling of the catalytic layer, resulting in a rapid decline in performance. For the samples after plasma oxidation, the regulation of surface functional groups makes electron transport more stable, while enhancing corrosion resistance and effectively inhibiting the loss of electrode active sites.
[0276] Experiment 4: Comparative experiment on the catalytic activity of electrode materials (Example 4 vs Comparative Example 4):
[0277] Purpose of the experiment:
[0278] This experiment aims to evaluate the effect of plasma oxidation activation treatment on the catalytic activity of nitrogen-doped graphene / carbon nanotube composites (N-G / CNTs), and focuses on analyzing the changes in specific surface area, charge transfer impedance, and redox catalytic performance.
[0279] Experimental procedure:
[0280] Preparation of Sample A (Example 4):
[0281] Raw material treatment: Weigh 2 g of N-G / CNTs and disperse it in 50 mL of ethanol / water (1:1) mixed solution, and ultrasonicate for 30 min.
[0282] Plasma oxidation activation: Put the material into the plasma treatment chamber (power 80 W, gas O2, treatment time 120 s).
[0283] Drying and post-treatment: The activated material is dried in vacuum at 80 °C for 6 h and reserved for use.
[0284] Preparation of Sample B (Comparative Example 4):
[0285] Without plasma treatment, directly use N-G / CNTs as the control sample, keeping all other experimental conditions the same.
[0286] Specific surface area test:
[0287] The BET nitrogen adsorption method is used to test the specific surface area and pore size distribution of the two samples to evaluate the change of catalytic active sites of the materials.
[0288] Charge transfer impedance (EIS) test:
[0289] Under the three-electrode system (Ag / AgCl reference electrode), test the Nyquist plot of the material in 1.0 M KOH solution and calculate the charge transfer resistance (Rct).
[0290] Catalytic performance evaluation (CV test):
[0291] The redox reaction (ORR) test was carried out by cyclic voltammetry (CV) with a scanning rate of 10 mV / s, and the peak current density and onset potential were recorded.
[0292] Long cycle test:
[0293] At a current density of 50 mA / cm 2 1000 charge-discharge cycles were carried out, and the discharge specific capacity, energy efficiency and Coulomb efficiency were recorded every 200 cycles.
[0294] Compare the long cycle stability of the plasma-treated sample (Example 4) and the untreated sample (Comparative Example 4).
[0295] Electrode morphology analysis:
[0296] The surface morphology of the electrode was observed by SEM to evaluate the structural integrity and stability of the catalytic layer.
[0297] XPS test was used to analyze the changes in functional groups on the electrode surface after long cycles.
[0298] Table 4: Effect of plasma oxidation treatment on the catalytic performance of N-G / CNTs
[0299]
[0300]
[0301] The role of plasma oxidation activation is not only surface modification, but more like a precise structure optimization process. Oxygen plasma will introduce functional groups such as hydroxyl and carbonyl groups on the material surface, resulting in local regulation of the electron cloud distribution. This regulation not only enhances the hydrophilicity of the material, but also increases the density of redox reaction (ORR) active sites, making the catalytic process more advantageous. From the EIS data, Rct decreases significantly after plasma treatment, indicating that electron transfer is smoother and the kinetics of the catalytic reaction is less hindered.
[0302] On the other hand, the change in specific surface area is particularly crucial. BET tests show that the specific surface area of plasma-activated N-G / CNTs increases by more than 30%, which means that more active sites are exposed. Although the untreated sample still has certain catalytic activity, the porosity of its structure is far less than that of the treated material, resulting in restricted reaction kinetics, a lower onset potential for ORR, and a significant decrease in peak current density. Plasma treatment not only optimizes the electronic structure, but also improves the pore network of the material, making the diffusion of reactants smoother, thus enhancing the overall catalytic performance.
[0303] The samples after plasma oxidation treatment have significantly better long-cycle performance than the untreated samples. After 1000 charge-discharge cycles, the capacity retention rate is still above 90%, while that of the untreated samples has dropped below 70%. This indicates that oxygen plasma activation not only optimizes the initial catalytic activity but also greatly delays the attenuation of electrode performance.
[0304] In terms of the attenuation rate, the attenuation rate of the plasma-treated samples is only 0.008%-0.009% / cycle, significantly lower than that of the untreated samples at 0.028%-0.031% / cycle. This shows that plasma oxidation effectively enhances the stability of the material, enabling it to maintain a high charge transfer efficiency during long-term cycling. For the untreated samples, the gradual loss of surface catalytic sites leads to a decrease in electrode activity, ultimately affecting the overall battery performance.
[0305] Experiment 5: Influence of electrolyte pH on the stability of the positive electrode reaction (Example 5 vs Comparative Example 5):
[0306] Experimental purpose:
[0307] This experiment aims to explore the influence of electrolyte pH on the positive electrode reaction kinetics and electrochemical stability, focusing on investigating the activity, charge transfer characteristics, and long-term cycling performance of the positive electrode material under different acid-base conditions to optimize the stability of the flow battery system.
[0308] Experimental procedure:
[0309] Sample A (Example 5, pH 2.5):
[0310] Electrolyte preparation: Prepare a 1.0 M H2SO4 + 0.1 M BTFQ solution and adjust the pH to 2.5.
[0311] Electrode treatment: Use carbon paper loaded with RuO2 as the positive electrode material, clean it, and dry it in vacuum at 80°C for 2 h.
[0312] Assembly of the system: Inject the electrolyte into the flow battery, set the flow rate at 10 mL / min to ensure uniform flow.
[0313] Sample B (Comparative Example 5, pH 5.0)
[0314] The electrolyte with the same ratio, but the pH is adjusted to 5.0, and other experimental conditions are kept the same.
[0315] Electrochemical tests:
[0316] Cyclic voltammetry (CV): The scanning rate is 20 mV / s, and the oxidation peak potential and reduction peak potential difference are measured.
[0317] Charge transfer resistance (EIS): Record the Nyquist plot and fit to calculate the Rct value.
[0318] Constant current charge-discharge cycle test: current density 50 mA / cm 2 , continuously cycle 500 times, and record the capacity retention rate.
[0319] Table 5: Influence of electrolytes with different pH values on the stability of the positive electrode reaction
[0320]
[0321] In an acidic environment, the electrochemical reaction is obviously more advantageous. In the system with pH 2.5, the oxidation peak potential is lower, indicating that the energy barrier of the electron transfer process is smaller and the reaction is more likely to occur. Moreover, the peak potential difference is narrower, meaning that the reversibility of the redox process is stronger. This situation is consistent with the decrease in the Rct value, indicating that the acidic condition effectively reduces the interfacial charge transfer resistance and makes the electrode reaction more efficient. In the pH 5.0 system, the oxidation peak potential increases significantly, the peak potential difference expands, and the Rct also increases substantially, indicating that the electron transfer process of the system is hindered and is not conducive to the reaction.
[0322] What is more worthy of attention is the cycling performance. Under acidic conditions, the battery capacity decay is extremely low and remains above 94% after 500 cycles. This shows that at low pH values, the structure of the positive electrode material is more stable and side reactions are inhibited. In the pH 5.0 system, the capacity decay reaches about 20%, indicating that in a weak acid environment, side reactions increase, the positive electrode material dissolves slowly, or impurities in the electrolyte form deposits, ultimately leading to a decrease in electrode activity.
[0323] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high energy density organic liquid flow battery, comprising a positive electrode electrolyte, a negative electrode electrolyte, an electrolyte solution, an ion exchange membrane and an electrode material, characterized in that: The positive electrode electrolyte contains a positive electrode active material, and its chemical structure is C 14 H8F6N2, containing trifluoromethyl and cyano substituents on the molecular skeleton, with a mass fraction of 2.0-5.0wt%; The negative electrode electrolyte contains negative electrode active material tetramethylpyridinium salt TMP + , whose structural formula is C9H 14 N + , the mass fraction is 1.5-4.0wt%; The electrolyte solution comprises 1.0-2.0M NaClO4 as a supporting electrolyte and a mixed solvent system of 10%-20% DMSO+H2O, and the volume fraction of DMSO does not exceed 25%; The ion exchange membrane is a sulfonated polyaryletherketone membrane, and the sulfonation degree thereof is 30%-50%; The electrode material is a nitrogen-doped graphene / carbon nanotube composite material with a nitrogen doping concentration of 2-10 at%, and its surface resistance is reduced to 3-5 Ω·cm after plasma oxidation activation treatment. 2 .
2. The high energy density organic flow battery according to claim 1, characterized in that: The oxidation-reduction potential of the positive electrode active material is in the range of 1.2-1.3V, and the oxidation-reduction potential of the negative electrode active material is in the range of -0.5 to -0.8V, so that the theoretical operating voltage of the battery reaches 1.5-2.0V.
3. The high energy density organic flow battery according to claim 1, characterized in that: The electrolyte solution further comprises a solubility enhancer of 0.1-0.5 M LiTFSI or a pH adjuster of 0.1-0.5 M H2SO4 or NaOH.
4. The high energy density organic flow battery according to claim 1, characterized in that: The ion exchange membrane adopts a plasma surface treatment process with a treatment time of 2-10 minutes and a power of 50-200W to optimize ion conductivity and reduce cross contamination of active substances.
5. A method for preparing an organic flow battery according to claim 1, characterized in that: The following steps are involved: S1, dissolving 2-amino-3-trifluoromethylpyridine (C6H4F3N2) and 1,2-dibromobenzene (C6H4Br2) in a solvent, adding a catalyst for electrochemical oxidation reaction, and synthesizing a positive electrode active material BTFQ; S2. Prepare the cathode electrolyte by solvent-induced self-assembly technology and prepare a 1.0-2.0 M NaClO4 electrolyte solution; S3, using sulfonated polyaryletherketone membrane as ion exchange membrane and performing plasma surface treatment; S4, using nitrogen-doped graphene / carbon nanotubes as electrode materials and performing plasma oxidation activation treatment; S5. Assemble the organic flow battery.
6. The preparation method according to claim 5, characterized in that: The electrochemical oxidation reaction in S1 was 0.5–2.0 mA / cm 2 The reaction is carried out at a current density of 50-80 °C, the stirring time is 4-6 h, and purification is performed by column chromatography or recrystallization to increase the purity of the positive electrode active material to >98%.
7. The preparation method according to claim 5, characterized in that: The solvent-induced self-assembly technology is used in S2 to optimize the solubility of the positive electrode active material by adjusting the solvent composition and the stirring rate of 200-500rpm to ensure that the solubility is >1.8M.
8. The preparation method according to claim 5, characterized in that: In S3, the sulfonated polyaryletherketone membrane is treated with oxygen plasma, and the optimized time is 2-10 minutes. After the treatment, the ionic conductivity of the membrane is increased to 0.05-0.1S / cm.
9. The preparation method according to claim 5, characterized in that: In S4, plasma oxidation activation technology is used to treat nitrogen-doped graphene / carbon nanotube composite electrode materials, the processing power is 50-200W, and the specific surface area after treatment reaches 500-800m 2 / g.
10. The preparation method according to claim 5, characterized in that: The assembly of the battery comprises: Filling the positive electrode electrolyte and the negative electrode electrolyte into corresponding storage tanks respectively; The electrolyte is delivered to the flow cell through a pipeline; Sulfonated polyaryletherketone membrane was used as the separator and nitrogen-doped graphene / carbon nanotube composite material was used as the electrode. The battery was assembled and charge and discharge tests were carried out.
Citation Information
Patent Citations
Organic phase oxidative reduction electrolyte and application thereof in flow battery
CN106654331A
Nonaqueous electrolyte and nonaqueous secondary battery
CN107408735A
High-energy-density alkaline iron-sulfur flow battery and preparation method thereof
CN115000480A
Ion exchange liquid membrane flow battery
CN116137339A
Lithium ion battery and electric appliance thereof
CN119627243A